Comparison of Clinical Features of Hepatitis B and C Virus-Related Hepatocellular Carcinoma - Luvsan, Ganchudur; Erdenebileg, Taivanbaatar; Mendjargal, Adilsaikhan; Baatarjav, Gan-Erdene; Damdinbazar, Otgonbayar; Enkhbat, Bayarmaa; Oidov, Baatarkhuu; Avirmed, Shiirevnyamba (Central Asian Journal of Medical Sciences, 2022)
Objective: To compare the clinical characteristics of hepatitis B virus-related hepatocellular carcinoma (HBV group) and C virus-related hepatocellular carcinoma (HCV group). Methods: By a single century, we analyzed the clinical characteristics of 23 patients with hepatitis B virus-related hepatocellular carcinoma (HBV group) and 34 with hepatitis C virus-related hepatocellular carcinoma (HCV group). Results: The patients in the HBV group (mean age 61.1 year) were about 6 years younger than those in the HCV group (mean age 67.1 year). Liver function, as measured by indocyanine green retention at 15 min, was better in the HBV group (17.5 %) than in the HCV group (25.4 %). A higher proportion of the HBV group (55 %) than the HCV group (44 %) had clinical stage I. T-factor differed significantly between the groups: 53 % of the HBV group were T3 - 4 compared with 41 % of the HCV group. Furthermore, a higher proportion of the HBV group was graded 2 - 3 for tumor thrombus in the portal vein (20.3 %) and had poorly differentiated hepatocellular carcinoma (7 %) compared with the HCV group (7.1 % and 5 % respectively). Univariate analysis identified poor prognostic factors for hepatocellular carcinoma as HBV, age < or = 50 year, clinical stage II-III, a high AFP level, higher number of tumors, larger tumor size, tumor thrombus in the portal vein 2 - 3 and in the hepatic vein 2 - 3. On multivariate analysis, poor prognostic factors were a high AFP level, a higher number of tumors, and tumor thrombus in the portal vein 2 - 3 and in the hepatic vein 2 - 3, but not HBV, age, clinical stage, or tumor size. In the multiple logistic regression models on the hepatitis infection, the OR for ASAT was 2.01 (95 % CI 1.41 - 6.91), statistically significant (p < 0.05). Conclusion: These results suggest that HBV itself is not a stronger prognostic factor than HCV.